The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1097/yic.0000000000000015
|View full text |Cite
|
Sign up to set email alerts
|

The discrepancy between patients and informants on clinician-rated measures in major depressive disorder

Abstract: Clinician-rated measures are used in clinical trials and measurement-based clinical care settings to assess baseline symptoms and treatment outcomes of major depressive disorder (MDD), with a widely held dictum that they are sufficient in assessing the patient's clinical status. In this study, we examined clinician-rated measures of depressive and global symptom severity, obtained by interviewing patients as well as informants in an attempt to examine the potential difference or similarity between these two so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…30,[94][95][96] The moderator analysis suggested that, in line with previous research, informant perspective moderates outcomes, with clinician reports generally documenting greater improvements than self-or parent-reports. 97 This highlights the need to ensure the views of patients themselves are considered wherever possible if patient shared decisions and empowerment are to be made a reality. 98 Problem type also moderated outcomes, with better outcomes for studies focused on depression than those for anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…30,[94][95][96] The moderator analysis suggested that, in line with previous research, informant perspective moderates outcomes, with clinician reports generally documenting greater improvements than self-or parent-reports. 97 This highlights the need to ensure the views of patients themselves are considered wherever possible if patient shared decisions and empowerment are to be made a reality. 98 Problem type also moderated outcomes, with better outcomes for studies focused on depression than those for anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include a brief assessment of social vulnerability (Social Vulnerability Scale; Pinsker, Stone, Pachana, & Greenspan, ; Pinsker, McFarland, & Stone, ) and an informant rating of cognitive decline (Informant Questionnaire on Cognitive Decline in the Elderly [IQCODE]; Jorm, ; Jorm & Jacomb, ). Similarly, providing a person with dementia the opportunity to comment on his or her subjective levels of anxiety, either through the use of a self‐rated assessment tool (e.g., Rating Anxiety in Dementia [RAID]; Shankar et al., ) or through simple interview questions, can assist with overcoming the poor congruence between informant and patient reports of affective symptoms (Peselow, Karamians, Lord, Tobia, & IsHak, ).…”
Section: Specific Uses For Shorter Form Assessmentsmentioning
confidence: 99%
“…Ein Beispiel ist der "Computerized Adaptive Diagnostic Test for Major Depressive Disorder" (CAD-MDD; Gibbons et al 2013). Beachtung verdient eine neuere Studie, wonach durch Kliniker erhobene MADRSund Clinical-Global-Impression(CGI)-Skalenwerte signifikant höher waren als durch Partner oder Angehörigeninterviews erhobene Ratings (Peselow et al 2013).…”
unclassified